Search for invisible decays of a Higgs boson produced through vector boson fusion in proton-proton collisions at √s = 13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier, 2019)
A search for invisible decays of a Higgs boson is performed using proton-proton collision data collected with the CMS detector at the LHC in 2016 at a center-of-mass energy , corresponding to an integrated luminosity of 35.9. The search targets the production of a Higgs boson via vector boson fusion. The data are found to be in agreement with the background contributions from standard model processes. An observed (expected) upper limit of 0.33 (0.25), at 95% confidence level, is placed on the branching fraction of the Higgs boson decay to invisible particles, assuming standard model production rates and a Higgs boson mass of 125.09 GeV. Results from a combination of this analysis and other direct searches for invisible decays of the Higgs boson, performed using data collected at , 8, and 13 TeV, are presented. An observed (expected) upper limit of 0.19 (0.15), at 95% confidence level, is set on the branching fraction of invisible decays of the Higgs boson. The combined limit represents the most stringent bound on the invisible branching fraction of the Higgs boson reported to date. This result is also interpreted in the context of Higgs-portal dark matter models, in which upper bounds are placed on the spin-independent dark-matter-nucleon scattering cross section.